The Ethics of Humanitarian Intervention - Parry, Jonathan (Taylor & Francis, 2024)
Few topics generate as much controversy and debate as armed humanitarian intervention. Military force involves death and destruction, as well as interfering in other countries’ domestic affairs. But, crucially, non-intervention is also controversial. When confronted with humanitarian crises abroad, many feel that outsiders are not only justified in using force to halt the abuses, but that they must do so. The Ethics of Humanitarian Intervention: An Introduction offers a guide to these ethical debates. In clear and informative style Jonathan Parry explores the following topics: